MARTIN Has Its Place: A Macroeconometric Model of the Australian Economy. Issue 314 (3rd March 2020) - Ballantyne, Alexander; Cusbert, Tom; Evans, Richard; Guttmann, Rochelle; Hambur, Jonathan; Hamilton, Adam; Kendall, Elizabeth; McCririck, Rachael; Nodari, Gabriela; Rees, Daniel M.
Abstract : This paper introduces MARTIN, the Reserve Bank of Australia's new model of the Australian economy. MARTIN is an economy‐wide model used for forecasting and counterfactual scenario analysis. In contrast to other models used at the Bank (and at many other central banks) which adhere to a narrow theoretical view of how the economy operates, MARTIN is a macroeconometric model that consists of a system of reduced‐form equations built to strike a balance between theoretical rigour and empirical realism. We provide an overview of the model, describe its main equations and demonstrate its responses to various scenarios.